Makna Ritus Kematian pada Etnis Bugis di Banten - Eva Syarifah Wardah; Romi Romi (Tsaqofah, 2019)
For the Bugis community in the Bugis Karangantu Banten village, death has a rite that is heavily colored by Islamic teachings. This is because death is the transition of human life from the real world to the mysterious realm, and Islam is believed to be a religion that can answer all mysterious problems after death. However, there are still some forms of ritual that appear to be inherited from pre-Islamic traditions. There are two unique rituals from the death rites of the Bugis Muslim community on the coast of Karangantu Banten, which are not found in the death rites of the Muslim community of Banten in general. First, the Mapasili rite which is performed on the 3rd day, and second, the Matampung rite which is generally performed on the 7th or 40th day, or after several months or one year has passed depending on the readiness of funds from the family of the deceased to perform the rite. this is because it costs a lot of money, such as a celebration or wedding ceremony. The Matampung rite is the biggest rite along the death rite for the Bugis people on the Karangantu coast, Banten